Art, nature, and religion in the central Andes : themes and variations from prehistory to present - Strong, Mary (Joe R. and Teresa Lozano Long Series in Latin American and Latino Art and Culture, 2012)
Taking a new approach to traditional Andean art that links prehistory with the present, this book illustrates the ongoing legacy of the past in contemporary art and the importance of art not only as a way of expressing religious ideas rooted in nature, but also as a means of resisting discrimination and oppression.